Potential Tsunami Inundation Model Using UAV at Palangpang Beach, Ciletuh-Palabuhanratu Geopark, Sukabumi, Indonesia - Katon Sena Ajie Nugraha (International Journal of Geotourism Science and Development, 2023)
Palangpang Beach is one of the popular locations in the Ciletuh-Palabuhanratu Geopark Area. This location has the potential for a tsunami because it is located at the southern coast of West Java and faces the southern subduction zone of Java. In addition, there are several active underwater faults that have the potential to trigger tsunamis, including the Cimandiri and Palabuharatu fault zones. The study discusses the simulation of tsunami inundation that can occur at Palangpang Beach. The estimation of the tsunami inundation zone is calculated with several variables, namely the roughness coefficient, the coastal morphology slope, and the tsunami's estimated run up. Imagery from the UAV can provide a more detailed picture of the roughness coefficient and slope of the beach. Based on calculations, it shows that Palangpang beach has a distant tsunami inundation zone, so that the area affected will be quite large. The tsunami inundation model can be used to create tsunami susceptibility zones and can be used to plan effective evacuation route.